Aquaporin-1: a major modulator of aging-mediated platelet/endothelial dysfunction in atherothrombosis. (25th November 2020) - Saeedi Saravi, S.S; Camici, G.G; Luscher, T.F; Beer, J.H
Abstract: Background: Aging is associated with development of cardiovascular diseases, including atherothrombosis. Aquaporin-1 (AQP1) is a water channel that also transports hydrogen peroxide (H2O2). Regarding to the role of oxidative stress in atherothrombosis, we hypothesized that AQP1 modulates aging-associated platelet/endothelial dysfunction. Methods: Human aortic endothelial cells (HAEC) from passages 5 (young) to 15 (senescent/old) were subjected to fluorescent immunocytochemistry to detect AQP1 protein expression and subcellular localization. The cells were also probed for AQP1 and the phospho/total proteins (AMPK, acetyl-coA-carboxylase (ACC), caveolin-1 and eNOS) for studying the signal transduction by immunoblotting. The endothelial cells were transfected with constructs containing H2O2 biosensor HyPer targeted to cell nucleus or cytosol followed by fluorescence imaging. The transcriptional levels of pro-inflammatory/pro-atherogenic vs. anti-inflammatory/atheroprotective genes in the cells were assessed by qRT-PCR. Human blood samples were taken and treated with or without AQP1 inhibitor (Bacopaside II, 10 μM) to examine the platelet adhesion and rolling velocity on vWF under high shear flow (100 dyn/cm 2 ). Also, platelet aggregation in response to collagen (2 μM), ADP (1 μM) and TRAP (1 μM) were recorded. Results: First, the senescence of HAEC was adjusted by a significant increase in β-galactosidase activity from passage 5 to 15. AQP1 immunofluorescence showed a remarkable increase in the young (P.5) compared to senescent (P.15) cells. Immunoblot analyses showed that aging leads to significant increases in AQP1 intensity and phosphorylation of caveolin-1 (Tyr14) and ACC (Ser79), along with decreases in phosphorylation of eNOS (Ser1177) and AMPK (Thr172) (p<0.01, n>6). Fluorescence imaging documented a robust H2O2 production in the senescent endothelial cell cytosol, but not nucleus, and activated TNF-α gene, whereas the transcription of hemoxygenase-1 gene enhanced in the young cells (p<0.01). AQP1 inhibition reduced platelet adhesion and thrombus formation, and elevated platelet rolling velocity on vWF under shear flow (p<0.01). Also, a decrease was found in platelet aggregation in response to AQP1 inhibition (p<0.05). Conclusion: These studies, for the first time, demonstrate that aging induces AQP1 expression in endothelial cells and platelets, and modulates the dephosphorylation of AMPK/eNOS. These may lead to platelet/endothelial dysfunction and production of pro-coagulant/pro-inflammatory factors via ACC activation. Therefore, AQP1 inhibition could potentially be exploited as a therapeutic strategy for improving age-related atherothrombosis. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): Swiss National Science Foundation (SNSF)